Effect of hatchery, genotype, month of hatching and number of eggs in one hatching unit on hatchability of hen, goose and duck eggs - Bene, Szabolcs; Benedek, Zsuzsanna; Polgár, J. Péter; Kovács, Gellért (GEORGIKON FOR AGRICULTURE, 2016)
The research was based on the national poultry hatching database, supplied by the Department of Animal Registration and Breeding Organization of the Hungarian National Food Safety Authority. Summarizing our previous works, the evaluations were extended to hen, goose and duck species - altogether 17 breeds and 27 hybrids -, 16146 hatching units, about 274.3 million eggs in year 2010. The effect of hatchery, genotype, month of hatching and number of eggs in one hatching unit on hatchability was analyzed by univariate analysis of variance (GLM). Phenotypic correlation coefficients were calculated between hatchability, hatching time and number of eggs in one hatching unit. The corrected overall mean values of hatchability of eggs of different poultry species were as follows: hen 82.96%, goose 61.56% and duck 64.59%. The differences between the genotypes in case of each species were significant. The meat and liver type hybrids showed lower hatchability than the mixed-use genotypes. The hatchability of goose eggs in summer months was almost 10% lower, than the mean value of the population. The hatchability of large units was approximately 8–10% better, than that of smaller units. Low, and significant correlation (r = -0.17–0.27; P < 0.01) was found in respect of the examined parameters. Based on the results it can be stated that, the longer is the hatching time, the worse is the hatchability of poultry eggs.